Court and Country: Discourses of Socio-political Collaboration in Northern and Southern Song China. (October 2016) - Levine, Ari Daniel
The Northern Song Empire (960–1127) was the most spatially integrated and bureaucratically centralized polity in the late medieval world, and its rulers articulated ideological claims to unitary and universal sovereignty. Both its monarchs and ministers shared a discourse of authority that postulated the throne as the only legitimate source of authority, which was not openly challenged by organized blocs of aristocratic, religious, or urban elites. Yet, the Northern Song Empire was much less autocratic in practice than in theory, since monarchs chose to delegate the making of state policy and the civil and military administration of the empire to a hierarchy of central, regional, and local officials, so that intra-bureaucratic dynamics limited arbitrary monarchical action. Using a micro-level case study of the abolition of the Green Sprouts rural credit policy (qingmiao fa 青苗法) in 1085–1086, this article analyzes the debates within the Northern Song imperial bureaucracy about the reach of state power. The court's anti-reformist high officials were united in their opposition to the policy, and individual ministers used a court-centered discourse of authority to denounce it for undermining the public good of the polity. Yet, its abolition required mobilizing extensive bureaucratic support within the central government and in local administration. By paying closer attention to the contexts and generic constraints of political rhetoric, and the intricacies of bureaucratic dynamics, it is possible to demonstrate more subtle fluctuations within the force fields of socio-political authority at court and in the country.